2008
DOI: 10.1117/1.2937476
|View full text |Cite
|
Sign up to set email alerts
|

Protoporphyrin IX fluorescence photobleaching increases with the use of fractionated irradiation in the esophagus

Abstract: Fluorescence measurements have been used to track the dosimetry of photodynamic therapy (PDT) for many years, and this approach can be especially important for treatments with aminolevulinic-acid-induced protoporphyrin IX (ALA-PpIX). PpIX photobleaches rapidly, and the bleaching is known to be oxygen dependent, and at the same time, fractionation or reduced irradiance treatments have been shown to significantly increase efficacy. Thus, in vivo measurement of either the bleaching rate and/or the total bleaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…Previous studies have shown the relationship between photobleaching of PpIX and cellular damage (22,25,33,39) and previous work within our group has linked changes in fluorescence intensity recorded with the non-invasive imaging system to clinical outcome (56). The greater the photobleaching of PpIX the greater the likelihood a complete clinical clearance of the lesion will occur.…”
Section: Relationship Of Ppix Accumulation and Dissipation With Patiementioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown the relationship between photobleaching of PpIX and cellular damage (22,25,33,39) and previous work within our group has linked changes in fluorescence intensity recorded with the non-invasive imaging system to clinical outcome (56). The greater the photobleaching of PpIX the greater the likelihood a complete clinical clearance of the lesion will occur.…”
Section: Relationship Of Ppix Accumulation and Dissipation With Patiementioning
confidence: 95%
“…A positive correlation has been previously demonstrated between PpIX photobleaching and cellular damage (22,25,32,33), indicating that the greater the level of photobleaching the more efficacious the PDT treatment. This finding indicated that greater PpIX accumulation increases the potential of the therapy as more PpIX is available for activation during irradiation.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous studies using fluorescence imaging have indicated that AK, BD and sBCC undergo similar fluorescence changes during MAL-PDT [23]. A positive correlation between PpIX photobleaching and cellular damage, and hence clinical efficacy of the treatment has also been previously demonstrated [25][26][27][28][29]. Therefore, we hypothesized here that if oxygen saturation could be manipulated positively (increased) with the employment of the OPI device, a difference in the level of PpIX photobleaching (greater amount) may have been detected which would ultimately affect clinical outcome (improvement).…”
Section: Discussionmentioning
confidence: 81%
“…A positive correlation between PpIX photobleaching and cellular damage has been previously reported [14][15][16][17] and it is therefore a good indicator of PDT effectiveness. The difference between the 'pre' and 'post' PpIX fluorescence readings can be attributed to PpIX photobleaching and so these measurements were quantified and compared as both the percentage of preirradiation PpIX levels bleached on irradiation as well as the absolute level of PpIX photobleaching in arbitrary units (Fig.…”
Section: Measurement Of Ppix Photobleachingmentioning
confidence: 89%